(untitled) - Perelman, Michael (New York, 2003)
From Adam Smith to the present day, economic theory has shortchanged the workers most crucial to the functioning of human life and offered skewed views of scarcity and extraction. Perelman shows how this approach has produced a discipline in which its followers' models and representations of the world around them are so removed from reality that continuing to abide by them would jeopardize both human capacities and nature itself.
Keywords: Smith, Adam, 1723-1790,Economics,Economics,Economic development,Income distribution,labor productivity,labor economics,Scarcity,value; Sociological aspects,Environmental aspects